The Challenges and Opportunities of Implementing Montessori Education in the Public Sector - David J. Fleming; Brooke Taylor Culclasure; Hannah Warren; Ginny Riga (University of Kansas, 2024)
Over the past two decades, Montessori education in the United States has rapidly expanded from the private to the public sector. This expansion has created important questions about whether or not the Montessori approach can thrive alongside the education standards and accountability movement in the public sector. Questions also exist as to precisely who is benefiting from this expansion of and investment in public Montessori. To examine these topics, this study focused on South Carolina, the state with the highest number of public programs in the United States. We used implementation surveys, classroom observations, and teacher interview data collected by the research team and student record data collected by the state of South Carolina to conduct the analysis, which consisted of three parts. First, we investigated to what extent public programs in South Carolina are able to implement Montessori education with fidelity to the model. Second, we considered what program characteristics were related to higher levels of Montessori implementation fidelity. Third, we analyzed which children had access to higher-fidelity Montessori programs. Generally, findings indicated that, despite challenges created by the education standards and accountability movement and concerns expressed by educators about authenticity, most programs in South Carolina were implementing Montessori with fidelity. Several characteristics were associated with higher levels of fidelity, including the age of the program. Findings also indicated that Black, Hispanic, and students from low-income families were disproportionately participating in lower fidelity programs. Our study provides an in-depth analysis of the challenges and opportunities associated with government trying to implement successful private-sector education models in the public sector.